Automation and robotics - Goyal, Khushdeep (New Dehli : S.K.Kataria & Sons, 2012)
The recent technological developments in the field of engineering have introduced exotic and complicated manufacturing systems and new products in the market. The intention of writing this book is to provide the students an insight into the new innovations with enough depth and breadth. The book is intended to provide a comprehensive knowledge in the fields of industrial automation, robotics and other related systems. Separate chapters have been devoted to introduction to robotics, elements of robotics, kinematics, robotic control, programming and robot applications. The short and objective type questions have been arranged chapter wise with answers provided. The students of both undergraduate and postgraduate colleges will find the book quite simple and informative (preface from the authors
1. Introduction; 2. Robot elements; 3. Robot coordinate systems and manipulator kinematics; 4. Robot control; 5. Robot programming; 6. Robot applications; 7. Automation; index
Keywords: Automobiles -- Electric equipment; Automobiles -- Electric equipment -- Maintenance and repair